Susceptibility-Weighted Angiography of Intracranial Blood Products and Calcifications Compared to Gradient Echo Sequence. Issue 5 (October 2013) - Docampo, Jorge; Gonzalez, Nadia; Bravo, Fernando; Sarroca, Daniel; Morales, Carlos; Bruno, Claudio
This study evaluated the sensitivity of susceptibility-weighted angiography (SWAN) compared with gradient echo (GRE) sequence in the depiction of haemorrhagic and calcium lesions by virtue of correlation analysis between the number, area and contrast index. The study included 21 patients (15 women, 6 men; age range 18 to 80 years) in whom intracranial haemorrhage or calcifications were previously diagnosed with CT and/or MR. GRE and SWAN sequences were performed as part of a conventional Brain MR study using a 3T scanner. Pathologic findings were: cavernoma (n=8), chronic intraparenchymal haemorrhage (n=5), petechial bleeding (n=3), parenchymal calcifications (n=2), sequelae of haemorrhagic contusion focus (n=1), post-surgical glioma (n=1) and venous angioma (n=1). In eight patients, more lesions were found in the SWAN sequence than in GRE. In the measurement of the largest area, in all cases the measured area was larger in the SWAN sequence than in GRE. The SWAN sequence was reported to have shown higher contrast between the lesion and the healthy white matter than in GRE. The SWAN sequence is more sensitive than GRE in the identification of cerebral haemorrhage and calcifications. The SWAN sequence also obtained significantly larger images than with GRE, and a higher contrast difference between the lesion and the healthy parenchyma.